PENDIDIKAN DEMOKRASI DALAM EVALUASI PEMILIHAN BUPATI DAN WAKIL BUPATI ROKAN HULU TAHUN 2015 - Abdul Putra Ginda Hasibuan; Safrudin Safrudin (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to look at democratic education in the Election of Regent and Deputy Regent of Rokan Hulu. Considering this is very important to do for theimprovement of democracy from the point of view of the future elections. To achieve these objectives the researcher did: first, the collected data will be analyzed descriptively qualitatively by taking the main points conveyed by the research subjects. Second, make an assessment and observation of the main data or additional data which is then adjusted to the real situation in the field. The results of the study indicate that the implementation of the Regent and Deputy Regent Election has been going well starting from every stage that has been regulated in the KPU's laws and regulations. Although there are still records of future improvements, namely the issue of participation which is still relatively low, the issue of recruitment of organizers at the lower level and the existence of a lawsuit over the results of the dispute at the Constitutional Court (MK). Therefore, improvements are needed in the implementation of the election of regents and deputy regents in order to achieve quality democracy.